Character Education Learning Model For Candidate Master Guide Based On Hypercontent - Jhoni Lagun Siang, Ismail Marzuki, Syaeful Bahri, Jafar Dahlan, I Ketut Ulianta, Lovely Lagunsiang (International Journal of Advanced Science and Technology, 2020)
Purpose of this research is to produce a hypercontent-based character education learning material product for candidate master guides. The methodology used is research and development methods. This study uses the jonnuro model which stands for Jhoni, Nurdin, and Robinson, this model consisting of three steps, namely planning, development, and evaluationt. The product test phase begins with the test of material experts, linguists, instructional design experts, and media experts. Then the product was tested to a number of candidate master guides, namely 3 candidate master guides for face to face trayout and 30 people for field trials. The results showed an average score of material experts 4.8 which meant the product was rated very good, a language expert 4.8 which meant the product was very good, a learning design expert 4.6 which meant the product was very good, and media expert 4, 2 which means the product is rated as good. Then in the trial phase of the candidate master guide the average results for the individual test stage were 98.7% which means the product was rated very well and at this stage the 97% field trial was considered very good. The results of the pretest and post test showed an increase in the percentage of mastery learning outcomes of students by 36,4 %. The percentage of students’ creativity tests for perception tests was 94.5%, knowledge tests were 95%, and abilities tests were 93.5%, so it can be concluded that the creativity of prospective master guides increased after studying-based learning material hypercontent. In conclusion, character education learning materials based hypercontent for prospective master guides are very good and need to be maintained because they can enhance the creativity of prospective master guides.